Intricacies of Upper Blepharoplasty in Asian Burden Lids - Paik, Ji Sun; Lee, Ji Hyeong; Uppal, Sandeep; Choi, Woong Chul (Facial Plastic Surgery, 2020)
Differences between Oriental and Caucasian eyelids have been explained in great detail in several reports in the past. The purpose of this article is to discuss the functional aspects of Asian double fold upper blepharoplasty and to present techniques that help to improve both the functional and cosmetic outcomes and satisfaction after surgery. The eyes of Asians are relatively small with thick skin in the eyelids and periorbital area. They typically lack the upper eyelid crease (creating the so-called double eyelid) due to burden factors like thick skin, hypertrophied orbicularis oculi muscle (OOM), submuscular fibroadipose tissue, thick orbital septum, abundant preaponeurotic fat, and lower positioned transverse ligament. Asian eyes may also have a superior visual field defect due to skin overriding the upper lid margin (skin–OOM–fat complex slide down). These burden factors result in the eyelashes appearing short and becoming misdirected and pressed toward the globe, causing functional discomfort. As a compensatory mechanism, Asian people tend to engage the frontalis muscle to lift the eyebrow to help them open their eyes. Along with aesthetic enhancement, double-eyelid surgery in Asian burden lids can improve the functional deficiencies helping the patients to open the eyes more easily. In addition, treatment of the Mongolian fold (medial epicanthal fold), caused by medial hypertrophy of preseptal OOM, augments the surgical results. In this report, we present the appropriate preoperative assessment, surgical technique, and postoperative care that should be employed to achieve consistently good functional and aesthetic outcomes in these patients.
Keywords: Asian eyelid; burden factors; upper blepharoplasty; Mongolian fold